PENGARUH MODAL SENDIRI DAN VOLUME USAHA TERHADAP SISA HASIL USAHA KOPERASI DI KABUPATEN BENGKALIS PERIODE 2013 s.d 2015 - Intan Permatasari; Makhdalena Makhdalena; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: this research aims to knowing and analyzing the influence of equity and business volume on the net income. The population in this research were all cooperatives registered in the Dinas Koperasi dan UMKM Kabupaten Bengkalis that have data (equity, business volume and net income) totaling 14 cooperatives with total years of observation 42. The data researched was obtained from the Dinas Koperasi dan UMKM Kabupaten Bengkalis. The data analysis technique used in this research is path analysis. The result of research indicated that the equity and business volume both simultaneosly and partially affect to net incomeKeyword : Own Capital, Business Volume and Net Income